Diabetes, microvascular complications, and cardiovascular complications: what is it about glucose? - Reusch, Jane E.B. (American Society for Clinical Investigation, 2003)
Glycemic control is the primary mediator of diabetic microvascular complications and also contributes to macrovascular complications. A new study (see related article beginning on page 1049) reveals a previously unrecognized association between oxidant activation of poly(ADP ribose) polymerase (PARP) and upregulation of known mediators of glycemic injury. Inhibitors of PARP may have potential therapeutic roles in the prevention of diabetic complications.